Fossil Weathering and Preparation Mimic Soft Tissues in Eocrinoid and Somasteroid Echinoderms from the Lower Ordovician of Morocco. (January 2020) - Saleh, Farid; Lefebvre, Bertrand; Hunter, Aaron W.; Nohejlová, Martina
Abstract: Abstract : Investigation of the Fezouata Shale has added to our knowledge on the initial diversification of metazoans. These Lower Ordovician deposits yielded abundant and diverse remains of cuticularized to lightly sclerotized organisms, in addition to numerous soft tissues. Described fossilized soft parts recovered from the Fezouata Shale belong mainly to arthropods. Soft tissues in echinoderms, a main component of the Fezouata Biota, remain largely unexplored. Here, we show that soft tissue-like impressions previously reported in eocrinoid and somasteroid echinoderms from this formation, are the results of modern weathering and fossil preparation that involved the use of latex molds: they do not reflect any original (soft) anatomical features of these organisms. These two examples suggest that reports of putative soft parts, especially in taxa with no current representatives, need to be thoroughly and critically evaluated.